Arti Baik Menurut George Edward Moore: Usaha Pemerintah Indonesia Mendukung Perdamaian Rusia-Ukraina: The Meaning of Good by George Edward Moore: The Indonesian Government's Business to Support Russia-Ukraine Peace - Astageni, Empi Siloka (Jurnal Filsafat Indonesia, 2024)
The focus of this article is to show the Indonesian government's efforts to support peace between Russia and Ukraine which are currently in conflict. The war between Russia and Ukraine had a serious impact on the lives of the global community. The efforts made by the Indonesian government contain good values in the diplomatic realm. These peace efforts are based on humanitarian grounds. The conflict between Russia and Ukraine has caused many casualties and damage here and there. The author wants to link the Indonesian government's support for peace with the concept of "good" according to George Edward Moore. "Good" itself was formulated by Moore as an abstract thing. Careful observation is needed to understand the meaning of "good". The "good" proposed by Moore in turn boils down to the actions produced by a person. Implicitly, "good" here refers to morality. The author finds that the steps taken by the Indonesian government are good. This decision is an awareness of the identity of the Indonesian nation as a collaborative entity. The Indonesian government also remembers its commitment to participate in implementing world order.